2023
DOI: 10.1186/s40580-023-00367-5
|View full text |Cite|
|
Sign up to set email alerts
|

Optical anisotropy of CsPbBr3 perovskite nanoplatelets

Abstract: The two-dimensional CsPbBr3 nanoplatelets have a quantum well electronic structure with a band gap tunable with sample thicknesses in discreet steps based upon the number of monolayers. The polarized optical properties of CsPbBr3 nanoplatelets are studied using fluorescence anisotropy and polarized transient absorption spectroscopies. Polarized spectroscopy shows that they have absorption and emission transitions which are strongly plane-polarized. In particular, photoluminescence excitation and transient abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…One possible explanation, as shown in Figure a, is that the clusters are intrinsically chiral due to the twisting of layered structures. Layered structure of the clusters has been suggested in our previous work ,, and by others. ,, As the clusters are very small, they may be distorted or strained, resulting in a twisted structure that happens to be chiral. Another possible explanation is defect-induced chirality, as illustrated in Figure b and found in previous studies of QDs.…”
mentioning
confidence: 58%
See 3 more Smart Citations
“…One possible explanation, as shown in Figure a, is that the clusters are intrinsically chiral due to the twisting of layered structures. Layered structure of the clusters has been suggested in our previous work ,, and by others. ,, As the clusters are very small, they may be distorted or strained, resulting in a twisted structure that happens to be chiral. Another possible explanation is defect-induced chirality, as illustrated in Figure b and found in previous studies of QDs.…”
mentioning
confidence: 58%
“…Another possible explanation is defect-induced chirality, as illustrated in Figure b and found in previous studies of QDs. Previous studies have found optical anisotropy within nanoplatelets and nanorods resulting from inherent defects during formation. ,, CsPbBr 3 perovskite nanoparticles were found to aggregate along a helical scaffold formed from either silica or polymers. , …”
mentioning
confidence: 91%
See 2 more Smart Citations
“…In the original publication of the article [ 1 ], the copyright holder was incorrectly given as ‘© Argonne National Laboratory, under exclusive licence to Korea Nanotechnology Research Society (KoNTRS) and Springer Nature Singapore Pte Ltd. 2023' but should have been ‘© Argonne National Laboratory'. This has now been corrected with this erratum.…”
mentioning
confidence: 99%